2017
DOI: 10.1242/jeb.148239
|View full text |Cite
|
Sign up to set email alerts
|

Tenacious D: Symbiodinium in clade D remain in reef corals at both high and low temperature extremes despite impairment

Abstract: Reef corals are sensitive to thermal stress, which induces coral bleaching (the loss of algal symbionts), often leading to coral mortality. However, corals hosting certain symbionts (notably some members of Symbiodinium clade D) resist bleaching when exposed to high temperatures. To determine whether these symbionts are also cold tolerant, we exposed corals hosting either Symbiodinium C3 or D1a to incremental warming (+1°C week −1 to 35°C) and cooling (−1°C week −1 to 15°C), and measured photodamage and symbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 41 publications
6
99
3
Order By: Relevance
“…The most thermoresistant colony (#3) had constitutively higher NF-κB levels and hosted a variety of Durusdinium symbionts as compared to thermosensitive colonies 1 and 2, which had lower NF-κB levels and hosted primarily Cladocopium symbionts. Several studies have reported that hosting Durusdinium is associated with increased thermotolerance in corals (e.g., Barshis et al, 2013;Silverstein et al, 2017;Gates, 2011, Davies et al, 2018). Whether host factors, such as increased NF-κB levels, also contribute to the bleaching resistance in our P. damicironis colony 3 is not clear at this time.…”
Section: Discussionmentioning
confidence: 99%
“…The most thermoresistant colony (#3) had constitutively higher NF-κB levels and hosted a variety of Durusdinium symbionts as compared to thermosensitive colonies 1 and 2, which had lower NF-κB levels and hosted primarily Cladocopium symbionts. Several studies have reported that hosting Durusdinium is associated with increased thermotolerance in corals (e.g., Barshis et al, 2013;Silverstein et al, 2017;Gates, 2011, Davies et al, 2018). Whether host factors, such as increased NF-κB levels, also contribute to the bleaching resistance in our P. damicironis colony 3 is not clear at this time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the P. Although partnerships with resistant Symbiodinium clades could afford greater bleaching resistance under extreme heat events (Silverstein, Cunning, & Baker, 2017), such evidence suggests that other factors may influence the conservation of associated and/or dominant symbiont lineages within these colonies. Though the focus of this study was not to assess clade assemblage at such fine resolution, it is important to consider that gradients of clade associations can afford varied environmental tolerances.…”
Section: Dna Isolation Amplification and Symbiont Variation Comparisonmentioning
confidence: 99%
“…Dinoflagellates in the family Symbiodiniaceae reside in the tissues of corals, giant clams, and other marine invertebrates, and have been empirically demonstrated to influence the ability of corals to survive stress events (Baker, 2001; Baker, Starger, McClanahan, & Glynn, 2004; Kenkel & Bay, 2018; Todd C. LaJeunesse et al, 2010; Todd C. LaJeunesse, Smith, Finney, & Oxenford, 2009; Manzello et al, 2018; Rouzé, Lecellier, Saulnier, & Berteaux-Lecellier, 2016). Particular Symbiodiniaceae species, such as Durusdinium trenchii , are more likely to remain associated with hosts and/or to retain photosynthetic function during acute temperature anomalies or extremes (Manzello et al, 2018; Silverstein, Cunning, & Baker, 2015; but see Silverstein et al, 2017). For example, in a dominant reef-building Pacific coral (Acropora millepora) , a Durusdinium species minimized bleaching (a diminished host health state characterized by loss of Symbiodiniaceae en masse) and increased host survival of acute thermal anomalies (Bay, Doyle, Logan, & Berkelmans, 2016; Berkelmans & van Oppen, 2006; A. M. Jones, Berkelmans, van Oppen, Mieog, & Sinclair, 2008; Mieog et al, 2009).…”
Section: Introductionmentioning
confidence: 99%